2017
DOI: 10.1136/openhrt-2017-000614
|View full text |Cite
|
Sign up to set email alerts
|

Smoking intensity and duration is associated with cardiac structure and function: the ECHOcardiographic Study of Hispanics/Latinos

Abstract: ObjectiveCardiovascular disease is the leading cause of death in smokers and this relationship is complicated by the multiplicity of cardiovascular effects of smoking. However, the relationship between intensity and duration of cigarette smoking and echocardiographic measures of right and left ventricular structure and function has been poorly studied.MethodsWe examined ECHO-SOL (Echocardiographic Study of Hispanics/Latinos) participants, a subset of the Hispanic Community Health Study/Study of Latinos. Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 42 publications
(32 reference statements)
2
22
1
2
Order By: Relevance
“…The results of this study contribute to the emerging body of evidence regarding the adverse effects of exposure to tobacco smoke on cardiac structure and function, which has primarily been studied in active current smokers. Within Echo-SOL, increased pack-years of tobacco smoking was associated with decreased systolic and diastolic function and increased cigarettes smoked per day were associated with increased LV mass 23. A study of the Coronary Artery Risk Development in Young Adults (CARDIA) cohort found that tobacco smoking was associated with a trend towards increased LV mass in all groups except for African-American men and increased LV stress in women; however, the echocardiographic variables in this study were limited to linear measurements, and 2D quantitation was not performed 24.…”
Section: Discussionmentioning
confidence: 98%
“…The results of this study contribute to the emerging body of evidence regarding the adverse effects of exposure to tobacco smoke on cardiac structure and function, which has primarily been studied in active current smokers. Within Echo-SOL, increased pack-years of tobacco smoking was associated with decreased systolic and diastolic function and increased cigarettes smoked per day were associated with increased LV mass 23. A study of the Coronary Artery Risk Development in Young Adults (CARDIA) cohort found that tobacco smoking was associated with a trend towards increased LV mass in all groups except for African-American men and increased LV stress in women; however, the echocardiographic variables in this study were limited to linear measurements, and 2D quantitation was not performed 24.…”
Section: Discussionmentioning
confidence: 98%
“…These findings reveal that cigarette smoking exposure may result in the development of cardiac dysfunction in a direct and continuous dose-dependent fashion and thus, may contribute to the heart failure epidemic. There were several previous studies regarding the relationship between smoking exposure and worsening cardiac function [1,6,[23][24][25]. Specifically, some studies reported that LV mass index could increase with higher exposure to smoking [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms regarding smoking exposure and cardiovascular dysfunction have been suggested previously. In animal models, cigarette smoking has been shown to induce ventricular hypertrophy and remodeling with increased serum levels of norepinephrine [6]. Continuous exposure to smoking could stimulate the autonomic nervous system and induce cardiac remodeling [6].…”
Section: Table 2 Echocardiographic Characteristics Of Participants Acmentioning
confidence: 99%
See 2 more Smart Citations